Keunggulan, Tantangan, dan Rekomendasi Kebijakan akan Pengembangan Energi Panas Bumi di Indonesia - Salma Zafirah Wisriansyah; Dorman Purba; Arnaldo Napitu (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
As a country that sits on the Pacific Ring of Fire, Indonesia has become the second largest geothermal power producer in the world. Geothermal energy is a clean-renewable energy that can help the country in reducing greenhouse gas emissions and secure its electricity supply in the future. Through Rencana Umum Energi Nasional (RUEN), government of Indonesia has set the target of building 7200 geothermal power plant capacity by 2025. However, per 2020, Indonesia has only built roughly about 2100 MW geothermal power plant capacity. This study aims to highlight geothermal’s advantages compared to other renewable energies and to discuss the biggest obstacle that had caused the sluggish development of geothermal power plant. This study is also expected to give strategic recommendations to the government to solve the biggest obstacle in developing geothermal power plant. The advantages of geothermal energy are environtmentally friendly, not intermittent, capable to be the base load, and doesn’t need a large area. This study argues that the biggest obstacle in developing geothermal power plant lies the exploration phase. Some actions had been taken by the government of Indonesia to support the exploration phase but this study believes that there are still some solutions that the government can take in order to be more supportive of geothermal exploration phase in Indonesia such as establishing geothermal-exploration entity, implementing depletion premium, and removing fossil fuel subsidy. These recommendations are expected to be capable in helping the government to achieve 7200 MW by 2025.